COMBINING DIGITAL FORENSICS AND BEHAVIORAL ANALYTICS TO STOP CYBERCRIMINALS: A DIGITAL FORENSIC PROFILING FRAMEWORK - Bwangah, Martin Luther (International Journal of Political Science and International Relations (IJPSIR), 2023)
This paper proposes a digital forensic profiling framework that combines digital forensics and behavioral analytics to identify and stop cybercriminals. With the increased use of digital services, cybercrime has become a significant challenge for law enforcement agencies. The study shows the need to include behavioral evidence analysis as part of the digital forensics examination to address criminal patterns in cybercrime, particularly social engineering attacks. The literature review covers cyber security challenges, digital transformation, and the adoption of digital forensics as a solution to emergent cybersecurity challenges. The paper explores the relationship between criminal profiling, behavioral analytics, and digital forensics. The research methodology includes a qualitative content analysis of academic peer-reviewed scholarly academic journals, theses, and doctoral dissertations authored or presented between 2001 and 2021 that addressed digital forensics and behavioral analytics. The study recommends the use of standardized investigation methods and the inclusion of human factors in digital forensic frameworks. In conclusion, the paper calls for the need for a more generalizable digital forensic method to address cyber security challenges in digitally dynamic organizations.